Kasih Karunia Dan Hukum Taurat Berdasarkan Titus 2:11-12 Bagi Transformasi Kerohanian Jemaat Kontemporer - Wennar, Wennar; Kusnadi, Hendric (EULOGIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
This study analyzes the concept of grace in Titus 2:11–12 by comparing it with the role of the Torah in shaping the spiritual life of contemporary congregations. Using a historical-grammatical exegetical approach and theological literature review, the research explores the meaning of grace within the Cretan cultural context and how it can be actualized in today's church communities. The findings reveal that grace in Christ not only offers forgiveness of sins but also acts as a transformative power that shapes Christ-like character and fosters a holy life. Grace transcends the limitations of the Torah, which merely exposes sin without empowering obedience. This study highlights how grace contributes to forming an inclusive, dynamic, and spiritually growth-oriented church community. As a new contribution, this research expands the understanding of grace beyond the individual level to include its collective role in shaping church communities. Practical implications include developing grace-based ministry programs, enhancing teaching effectiveness, and empowering believers to serve as an active response to God's love.